Isoniazid Induced Psychosis: A Case Report - Kaur, Taranjeet; Kaur, Kanwalpreet; Malhotra, Preeti (Journal of Nepal Paediatric Society, 2019)
Psychosis is a state of altered behaviour and mentation and it is not common in children. Isoniazid is a commonly used drug in the treatment and prophylaxis of tuberculosis. It may cause psychosis if overdosed but rarely with usual recommended doses. We report a case of drug induced psychosis secondary to isoniazid intake in a seven years old boy, who exhibited psychotic features about 10 days after the commencement of anti-TB combination drugs (Directly Observed Treatment Shortcourse) containing Isoniazid. This patient had no past medical or family history of mental illness. Drug induced psychosis was a possibility, and the responsible drug (isoniazid) was stopped. He improved following the withdrawal of isoniazid. Isoniazid psychosis is a major complication as iatrogenic psychiatric complications can greatly impact the patients’ quality of life, which if recognised early can be effectively treated.